THE EFFECTIVENESS OF THE IMPLEMENTATION OF AN ACCENTUATED METHODOLOGY FOR THE DEVELOPMENT OF THE PHYSICAL STATUS OF YOUNG BASKETBALL PLAYERS (Scientific journal of the Fergana State University, 2024)
The article presents the results of a pedagogical experiment aimed at identifying the effectiveness of an accented methodology for developing the physical status of young basketball players at the initial stage of sports improvement.